A water management model for lowland paddy irrigation systems - Gilles, Bienvenido Cruz; Apichart Anukularmphai; Eggers, Helmut; Olesen, Svend Elsnab; Early, Alan C.; Switzerland (Bangkok : Asian Institute of Technology, 1980)
An irrigation system, after it has been designed and built must be managed. Management, often called operations and maintenance (0 & M), must be organized around the physical components of a system, which are specified by design. To emphasize the operational aspect of management, a water management model was developed for lowland paddy irrigation systems. It can be utilized either as a prediction-correction model or a simulation model depending on which function is specified. As a prediction-correction model, it makes daily inventory of areas under different farming activities on a weekly basis and provides field operational guidelines for executing water deliveries for each of these areas. The model can also be utilized to simulate the operation and response of an irrigation system to different system-wide and on-farm management schemes and its combinations. The system-wide management strategies that the model can handle are: simultaneous irrigation, rotational irrigation by lateral canal and rotational irrigation by tertiary turnout. On-farm management is related to the paddy spillway height management. Two component models were. developed and incorporated in both prediction -correction and simulation procedures of the model. The area inventory component model was designed to account for areas under different farming activities. This information was utilized by the distribution network component model in accounting for water entering or leaving an irrigation system. A correction procedure was applied on both component models to control the operation of the models. This was done through weekly feedback. The water balance equation governs the computation of the demand for both predicted and correction deliveries. For simultaneous irrigation, water delivery scheduling is based on a predetermined critical depth, i.e. minimum depth of water in the paddy before irrigation is required. For both rotational irrigation by later' al canal and rotational irrigation by tertiary turnout, the irrigation schedule is fixed by the number of days in the rotation period. In all cases, a rainfall-use efficiency criteria was applied such that irrigation is treated as a supplement to rainfall. Test runs of the model were made for both prediction-correction and simulation procedures utilizing the data from the Lower Talavera River Irrigation System (LTRIS) located at Central Luzon, Philippines. The results of the simulation show that: (a) effective rainfall is determined by the daily intensity and distribution of rainfall, number of days between irrigation application and the ability of the paddy to trap rainfall; (b) improvement in effectiveness of rainfall due to increase in paddy spillway height does not necessarily mean more water savings since the water requirement of the paddy is also increased. The computer program is written in FORTRAN IV H-Extended. The program listing may be obtained from the Division of Agricultural and ·Food Engineering, Asian Institute of Technology, Bangkok, Thailand or from the Irrigation and Water Management Department, The International Rice Research Institute, College, Laguna, Philippines.
A thesis submitted in partial fulfilment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1980
Keywords: Irrigation farming